Revealing the Smartphone Purchasing Behavior of Umsida Students : Mengungkap Perilaku Pembelian Smartphone Mahasiswa Umsida - Fernata, Farhan; Cahyana , Atikha Sidhi (Indonesian Journal of Innovation Studies, 2024)
This study investigates the factors influencing smartphone purchasing decisions among Umsida students, focusing on product quality, price, brand, and promotion. Using a quantitative approach with 140 respondents and Structural Equation Modeling (SEM) analysis, the research found that while product quality and price had no significant impact on purchasing decisions, promotion and brand significantly influenced students’ choices. These findings offer valuable insights for marketing strategies targeting this demographic, suggesting a need to prioritize promotional efforts and brand positioning to enhance consumer engagement and decision-making processes among Umsida students. Highlight: Quantitative Analysis with SEM: Rigorous methodology for smartphone purchasing factors among Umsida students. Promotion and Brand Impact: Crucial influencers in Umsida students’ smartphone buying decisions. Marketing Insights: Prioritize promotion and brand for effective Umsida student engagement. Keyword: Smartphone Purchasing Decisions, Umsida Students, Product Quality, Promotion, Brand Influence